Neurological Manifestations of Systemic Lupus Erytematosus - F. J., Hernández Ramos,; F. J., Hernández Chamorro,; M., Medina Rodríguez,; A., Palomino García,; M.D., Jiménez Hernández, (International Journal of Innovative Research in Medical Science, 2020)
Systemic lupus erythematosus (SLE) is the prototype of autoimmune disease with multisystemic damage capacity. Its diagnosis is based on clinical and immune criteria, which have been recently updated by EULAR/ACR, making positive antinuclear antibodies (ANA) a necessary part of the diagnosis criteria. Those criteria are responsible for the decrease in the neurological manifestations, in comparison with the former criteria. Eighty seven LES patient’s retrospective hospital sample. Sociodemographic variables, autoimmune family history, years of evolution, diagnosis, antibodies, neurological clinic, image tests, electroencephalography and cerebrospinal fluid, treatment and obtained score according to EULAR/ACR criteria are being analysed. Seventy patients and seventeen with other diagnosis are obtained, where 84.3% are women with an average age of 44.64 years, no autoimmune family history in 54.70% of the cases, an average of 15.3 years of evolution, 100% of ANA and 75% antiDNA positives. Headache, seizures, strokes and cognitive impairment are the most common neurological manifestations. 78.6% of them lack an image test, where steroids are the most used immunosuppressor (58.24%), followed by hydroxychloroquine (48.6%). The frequency of the discussed neurological manifestations is similar to the one present in current literature, having cognitive decline a low prevalence. Our sample’s neurological manifestations lack of statistical significance for SLE diagnosis, being anti-DNA antibodies are crucial for it. We suggest that a prospective study with less years of evolution, widening the neurological manifestations and having anti-DNA antibodies as entry criterion, can increase statistical significance.